Analysis of epoxy functionalized layers synthesized by plasma polymerization of allyl glycidyl ether. Issue 30 (19th July 2018) - Manakhov, Anton; Fuková, Šárka; Nečas, David; Michlíček, Miroslav; Ershov, Sergey; Eliaš, Marek; Visotin, Maxim; Popov, Zakhar; Zajíčková, Lenka
Abstract : The deposition of epoxide groups by plasma polymerization opens new horizons for robust and quick immobilization of biomolecules on any type of substrate. Abstract : The deposition of epoxide groups by plasma polymerization opens new horizons for robust and quick immobilization of biomolecules on any type of substrate. However, as of now there are just very few papers dealing with the deposition of epoxy layers by plasma polymerization, probably due to the high reactivity of this group leading to a low functionalization efficiency. In this work we carried out an extensive experimental and theoretical investigation of plasma synthesis of epoxide groups from a low pressure allyl glycydyl ether (AGE) plasma. The influence of composite parameter W/F and the working pressure on the density of epoxide groups and the layer stability was thoroughly addressed. It was found that by increasing the working pressure it is possible to sufficiently raise the concentration of epoxide groups. The composite parameter W/F was shown to be a crucial parameter in affecting the density of epoxides. An optimal value of W/F of around 2.3 eV per molecule leading to the highest density of epoxides produced in the process at 15 Pa was revealed through FT-IR and XPS findings. This value correlates well with the ab initio calculations suggesting that the lowest bond dissociation energy belongs to the C–O bond of the epoxide ring. Therefore, in order to increase the density of epoxides deposited by plasma polymerization, a precursor molecule containing at least two epoxide rings is strongly advised to be employed.